Dwarf Mistletoe on Blue Pine in the Western Himalayas and its Control - Bakshi, B. K.; Puri, Y. N. (Indian Forester, 1971)
Dwarf mistletoe is causing economic damage to blue pine, particularly in the low rainfall and arid locations in Himachal Pradesh and Jammu and Kashmir States. Dispersal of the parasite, its mode of infection, symptoms of the disease and damage to the host are described. In high level blue pine forests where incidence of infection is heavy resulting in stunted growth and mortality, it appear. Unprofitable to continue with such stands. It is suggested that such forests be carefully examined and clearfelled wherever feasible from the point of soil and moisture conservation and site maintenance and artificially regenerated. Burning after clearfelling may help regenerations in locations where the disease incidence is low, the disease may be kept in check through sanitation and its spread checked by establishment of a protective zone. These are the usual measures adopted in other countries to control dwarf mistletoe.